The 8th International Electronic Conference on Sensors and Applications 2021
DOI: 10.3390/ecsa-8-11266
|View full text |Cite
|
Sign up to set email alerts
|

Amide I Band Analysis Applied to Vibrational Micro-Spectroscopies of Gingival Crevicular Fluid Samples for Orthodontic Treatment Monitoring

Abstract: Vibrational micro-spectroscopies were applied to investigate the gingival crevicular fluid (GCF) for monitoring orthodontic treatment with fixed appliances. The GCF samples were investigated using Fourier transform infrared, Raman, and surface-enhanced Raman micro-spectroscopies. The GCF spectra collected at different times of orthodontic tooth movement were used to characterize the biochemical changes occurring during the treatment. We examined the amide I band region by means of deconvolution analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that an unfolding process occurs during the initial stage of orthodontic treatments followed by some recovery during the following days. Modifications could also result from the formation of amyloid aggregates that can be induced by mechanical stress due to the application of orthodontic forces [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that an unfolding process occurs during the initial stage of orthodontic treatments followed by some recovery during the following days. Modifications could also result from the formation of amyloid aggregates that can be induced by mechanical stress due to the application of orthodontic forces [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among a large number of physical and chemical assessment techniques, spectroscopy-based methods are gaining increasing importance thanks to technological progress and the growing knowledge of inherent phenomenology. In this work, we used Fourier Transform Infrared and Raman microspectroscopy ( -FTIR and -RS), and Surface-Enhanced Raman Spectroscopy (SERS) for investigating human gingival crevicular fluid (GCF) samples, as preliminarly reported in a communication at the 8th Electronic Conference on Sensors and Application (ECSA 8) [ 1 ]. Both -FTIR and -RS techniques allow us to extract information on chemical bonds and secondary protein structure from very small quantities of the sample [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we used Fourier Transform Infrared and Raman microspectroscopy ( -FTIR and -RS), and Surface-Enhanced Raman Spectroscopy (SERS) for investigating human gingival crevicular fluid (GCF) samples, as preliminarly reported in a communication at the 8th Electronic Conference on Sensors and Application (ECSA 8) [ 1 ]. Both -FTIR and -RS techniques allow us to extract information on chemical bonds and secondary protein structure from very small quantities of the sample [ 1 , 2 , 3 , 4 , 5 ]. However, the involved mechanisms of these two techniques are different, and complementary information can be obtained.…”
Section: Introductionmentioning
confidence: 99%